Agomelatin's Effect on Parkinson Disease Model on Rats - Pınar Ayvat; Ayse Saide Sahin; Burak Cem Soner (Galenos Publishing House, 2019)
INTRODUCTION: Parkinson disease is one of the most common neurodegenerative disorders. This disease still have no exact cure. Agomelatin is the synthetic analog of melatonin hormone that is synthesized in pineal gland and then released from there. Agomelatin shows its antidepressant effects on central nervous system (CNS) by activating MT1 and MT2 receptors caused by melatonin and by antagonizing serotonin 5-HT2C receptors caused by monoamine. In this study, we examined the effects of oral Agomelatin administration on rats, which had experimental Parkinson disease formed by utilizing 6-OHDA. METHODS: We administered unilateral intrastriatal 6-OHDA on 45 rats weighing 270-330 gr, in three different groups. We applied dissolver on control group; in other two groups we administered 5 mg/kg/day and 20 mg/kg/day Agomelatin respectively, for 15 days. At the end of this treatment process, motor coordination and skills were tested with sticky band test, open-field test and cylinder test, whereas, dopaminergic damage degree was tested with apomorphine induced rotation test. RESULTS: In our study, we found out that in both groups in which Agomelatin was administered (5 mg/kg/day and 20 mg/kg/day respectively), Agomelatin prevented progression of experimental Parkinson disease formed with 6-OHDA in rats. DISCUSSION AND CONCLUSION: Agomelatin showed a protective effect on striatal neurons damage in experimental Parkinson's Disease model.